Doctor strange (2018), volume 1 ebook - Waid, Mark (Doctor Strange (2018), 2024)
Collects Doctor Strange (2018) #1-11. Earth's Sorcerer Supreme goes intergalactic! When Stephen Strange loses his mastery of the mystic arts, Tony Stark offers a twenty-first-century solution: Search for new magic in outer space! Bizarre new spells, allies and enemies await Strange beyond the stars as he uncovers corners and secrets of the Marvel Universe never before witnessed! But he's a little out of his element traveling the galaxy - and it shows! Before long, Strange finds himself powerless, friendless and the prisoner of a hostile civilization. Thankfully, a new companion can lend a hand when the Super-Skrull swings by, wielding the Time Stone! But what shocking surprise is waiting for Stephen back on Earth? It's time to gear up, get serious and build a new arsenal - because Doctor Strange has become his own worst enemy!